The Sydney Medically Supervised Injecting Centre: a controversial public health measure - Cate Kelly; Katherine M. Conigrave (Elsevier, 2002)
Abstract Background: Injecting drug use remains a major public health concern, particularly because of opiate overdose and transmission of blood‐borne viruses. Sydney's Medically Supervised Injecting Centre (MSIC) opened on a trial basis in May 2001 in an effort to reduce the harms of drug use. In this report, we provide a brief overview of the reported public health impact of supervising injecting facilities (SIFs) and review the history and early process evaluations of the Sydney Centre. Methods Medline, Internet searches and perusal of bibliographies of articles were used to identify key English language publications on SIFs. These were supplemented by interview with the Medical Director of Sydney MSIC, Dr Ingrid van Beek. Discussion and conclusions: It is difficult to be certain of the public health impact of SIFs but evidence from overseas and Sydney's early process evaluations provide promise that they may make a positive contribution to health.